Isolation of umbelliferone from leaves of Conocarpus erectus L. cultivated in Iraq - Tahany Amir Tawfeeq; Ghaith Ali Jasim; Abdulmutalib A. Nasser (College of Pharmacy / Mustansiriyah University, 2022)
Conocarpus erectus L. is a perennial, evergreen shrub belonging to Combretaceae family. In this study we investigate the phytoconstituents in the leaves of C.erectus. Preliminary tests of alcoholic extract proved the presence of flavonoids, coumarins, saponin, terpens, tannin and absence of alkaloids. Umbelliferone was detected in the ethyl acetate fraction of the extracted plant by TLC and isolated as a light yellowish powder by preparative TLC. Identification of it was done by HPLC, HPTLC and chemical structure elucidated by IR and UV.